The Influence of Financial Literacy, Financial Self-Efficacy and Fintech Payment on the Financial Behavior of QRIS Users - Yanti, Resti Dwi; Suryadi, Edy (GoAcademica Research & Publishing, 2024)
Financial behavior is very important to describe how a person acts on financial decision-making. Finance needs to be managed in a planned and organized manner so that the goals that have been prepared can become a reality. The purpose of this research is to find the effect of financial literacy, financial self-efficacy and fintech payment on financial behavior using QRIS. This research uses associative research. The sample used in this study were 150 QRIS users specifically for people in Pontianak City who were taken based on criteria. The data collection technique used a questionnaire distributed to respondents. The results of the study revealed that financial literacy owned by individuals as well as financial self-efficacy and fintech payment have a positive and significant effect on the financial behavior of people in Pontianak City who use QRIS.